2020
DOI: 10.1111/jce.14689
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with corticosteroids is associated with an increase in ventricular arrhythmia burden in patients with clinically manifest cardiac sarcoidosis: Insights from implantable cardioverter‐defibrillator diagnostics

Abstract: Introduction: We sought to explore the relationship between ventricular tachycardia (VT) and premature ventricular complex (PVC) burden (from implantable cardioverter-defibrillator diagnostics), before and during corticosteroid use in patients with newly diagnosed clinically manifest cardiac sarcoidosis (CS). Methods: A single-centre, prospective cohort study was performed in consecutive patients who met all of the following criteria: (1) presentation with clinically manifest CS, (2) abnormal myocardial fluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…100,101 Moreover, Medor et al reported a threefold increase in premature ventricular contraction and a significant increase in nonsustained VT after initiating corticosteroids compared with pretreatment in patients with symptomatic CS and active inflammation on PET scan. 102 This was in accordance with the study of Banba et al 21 Of note, Yodoga et al reported no significant difference in the number of premature ventricular contractions and nonsustained VT after initiating corticosteroids in their entire cohort but most patients included did not present active inflammation on nuclear imaging. 103 Methotrexate can be used as a second-line therapy when corticosteroids are not effective or if there are significant side effects.…”
Section: What Is the Role Of Immunosuppressive Therapy In Cs?supporting
confidence: 86%
“…100,101 Moreover, Medor et al reported a threefold increase in premature ventricular contraction and a significant increase in nonsustained VT after initiating corticosteroids compared with pretreatment in patients with symptomatic CS and active inflammation on PET scan. 102 This was in accordance with the study of Banba et al 21 Of note, Yodoga et al reported no significant difference in the number of premature ventricular contractions and nonsustained VT after initiating corticosteroids in their entire cohort but most patients included did not present active inflammation on nuclear imaging. 103 Methotrexate can be used as a second-line therapy when corticosteroids are not effective or if there are significant side effects.…”
Section: What Is the Role Of Immunosuppressive Therapy In Cs?supporting
confidence: 86%
“…Therefore, corticosteroid therapy has been reported to have a beneficial effect on ventricular arrhythmias by suppressing disease inflammation in patients with CS 3 4. However, corticosteroid was also reported to increase the burden of ventricular arrhythmias,15–17 and this mechanism is poorly understood. In contrast, during the chronic phase, it is likely that macro re-entry circuits around cardiac scarring cause VT 5 6.…”
Section: Discussionmentioning
confidence: 99%
“…4 14 Therefore, corticosteroid therapy has been reported to have a beneficial effect on ventricular arrhythmias by suppressing disease inflammation in patients with CS. 3 4 However, corticosteroid was also reported to increase the burden of ventricular arrhythmias, [15][16][17] and this mechanism is poorly understood. In contrast, during the chronic phase, it is likely that macro re-entry circuits around cardiac scarring cause VT. 5 6 Cardiac scarring has been reported to extend not only to the endocardium, including the left and right ventricles, but also to the epicardium, 1 4 which may be challenging to ablate in ill-equipped facilities.…”
Section: Case Reportmentioning
confidence: 99%
“…However, a significant reduction in PVCs and NSVT was observed in patients with less advanced LV dysfunction (EF ≥35%). Contrary to the expected positive effect, an increased ventricular arrhythmia burden with corticosteroid treatment has also been reported 41. However, the effects of individual immunosuppressive agents, such as third-line drugs, might not be the same as the effect of steroids on ventricular arrhythmia 42…”
Section: Treatmentmentioning
confidence: 99%